Assessing carbon emissions of the innovative renovation project of Yihe Bridge on Beijing Road - Xian Li; Jianzhuang Xiao; Liangyu Zhu; Dengyuan Zhu; Xiaoyuan Song; Yuanxin Liu; Wei Hua (Low-Carbon Materials and Green Construction)
Abstract Carbon emissions from engineering construction play a critical role in achieving urban carbon peak and neutrality goals. This study evaluates the carbon emission reduction benefits of the renovation project of Yihe Bridge on Beijing Road using a life cycle assessment (LCA) approach. The carbon emissions resulting from the renovation were compared with those of an alternative demolition and reconstruction plan. The calculation boundary for carbon emissions during the bridge construction period was defined based on the renovation project’s specifics, dividing the process into three stages: material production, material transportation, and mechanical construction. By integrating factor decomposition theory with the carbon emission factor method, a carbon emission mode was developed, allowing a comprehensive quantitative analysis for the construction period. Results indicate that total carbon emissions were 84 560.40 t, with material production contributing 94.73%, transportation 1.47%, and mechanical construction 3.80%. The carbon emission intensity of the newly expanded bridge section was 2.11 t/m2. Compared to the demolition and reconstruction, the renovation plan reduced carbon emissions by 53 643.44 t, achieving a 38.81% reduction.